CULTURAL AND ART PROGRAMS: BASES OF EDUCATING TECHNOLOGY AND PREPARATION OF TEACHERS OF ARTISTIC DISCIPLINES TO ITS REALIZATION AT SCHOOL (Pedagogy of Higher and Secondary Education, 2007)
In the article are examined the substantive conceptual positions of the author educating technology «Cultural and art programs». Author lights theoretical, methodical and organizational national aspects of preparation teachers of artistic disciplines to the mastering of this technology.
Keywords: cultural and art programs; technologies; educating process; artistic disciplines